2003
DOI: 10.1002/pits.10127
|View full text |Cite
|
Sign up to set email alerts
|

Relaxation and guided imagery: A school‐based intervention for children with asthma

Abstract: Asthma, a disease of the respiratory system, is the most common chronic medical condition among children. School-aged children with asthma evidence increased absenteeism, decreased school performance, restriction of various activities, poor peer relationships, and emotional and behavioral difficulties. Asthma can be triggered and exacerbated by emotions and stress, and therefore, it has been treated with psychological interventions. Relaxation and guided imagery (RGI), an intervention based on the theoretical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 48 publications
1
22
0
Order By: Relevance
“…The findings are consistent with those of Peck et al (2003), who studied the effects of relaxation and guided imagery in a middle school population. The present study indicated that not only is relaxation and guided imagery a valuable treatment for improving the lung functioning of much younger children, but that these children are able to comprehend and enjoy the treatment as much as adolescents do.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The findings are consistent with those of Peck et al (2003), who studied the effects of relaxation and guided imagery in a middle school population. The present study indicated that not only is relaxation and guided imagery a valuable treatment for improving the lung functioning of much younger children, but that these children are able to comprehend and enjoy the treatment as much as adolescents do.…”
Section: Discussionsupporting
confidence: 93%
“…This study reported an increase in FEV 1 (large airway functioning) levels following baseline for all the participants, indicating that RGI is a positive adjunct to the pharmacological treatment of asthma. The current study was intended to serve as a replication and extension of Peck et al (2003). Relaxation and guided imagery with children with asthma has not been studied thus far in the elementary school grades.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Studies with adult asthma patients have also demonstrated improved lung function and reduced anxiety, as well as decreased symptom severity and increased self-efficacy (Freeman, 1998). Peck, Bray, and Kehle's (2003) RGI treatment aided in establishing a sense of control over lung function in middle school children. The treatment involved engaging in relaxation exercises while imagining the internal healing of one's lungs.…”
Section: Psychological Interventionsmentioning
confidence: 99%
“…5. School-based interventions have resulted in improved lung functioning in students with asthma (Bray et al, , 2006Peck et al, 2003 …”
Section: Implications For Practitionersmentioning
confidence: 99%